Branding and place image on the example of the capital city of Warsaw - Śleszyńska-Świderska Anna (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2023)
The image of a city is the ultimate product and is formed in the course of activities that are a process. A city wishing to achieve market success should strive to shape a positive image. In this aspect, it is necessary to regularly study the image of the perceived city. The identity and brand of the city play a fundamental role in this. The purpose of this article is to identify the image of Warsaw promoted by local authorities and the perceived image of the city among its residents. The thesis that has been verified is that there is no full correspondence between the image of Warsaw promoted by the local authorities and the image of the city in the consciousness of its residents. The article consists of three parts. The first discusses the concepts of identity, brand and image of the city. The second characterizes the brand of the capital city of Warsaw and its components. And in the third, the perceived image of the capital city of Warsaw is presented. Such research methods as literature studies, analysis of internal documentation of the Warsaw City Hall in the form of reports and reports in the area of image issues, analysis of source documents in the form of the city development strategy, analysis of reports and reports on promotional and image issues of cities in national and international dimensions, and deductive analysis were used. The considerations carried out showed allowed positive verification of the thesis. In addition, they showed that a positive image of a city is an important factor in its development. Wizerunek miasta jest produktem ostatecznym i kształtuje się w toku działań mających charakter procesowy. Miasto, pragnące osiągnąć sukces rynkowy, powinno dążyć do kształtowania pozytywnego wizerunku. W tym aspekcie konieczne jest regularne badanie wizerunku postrzeganego miasta. Zasadniczą rolę odgrywa tu tożsamość i marka miasta. Celem artykułu jest identyfikacja wizerunku Warszawy promowanego przez władze lokalne oraz postrzeganego wizerunku miasta wśród jej mieszkańców. Potwierdzona została teza, że nie ma pełnej zgodności pomiędzy wizerunkiem Warszawy promowanym przez władze lokalne a wizerunkiem miasta w świadomości jego mieszkańców. Artykuł składa się z trzech części. W pierwszej omówiono pojęcia tożsamości, marki i wizerunku miasta. Druga charakteryzuje markę m.st. Warszawy i jej elementy składowe. W trzeciej zaś przedstawiono postrzegany wizerunek miasta stołecznego Warszawy. W artykule wykorzystano następujące metody badawcze: analiza literatury, analiza dokumentacji wewnętrznej Urzędu m.st. Warszawy w postaci raportów i raportów w obszarze zagadnień wizerunkowych. Ponadto analizie poddano dokumenty źródłowe w postaci strategii rozwoju miasta, dotyczących zagadnień promocyjnych i wizerunkowych miast w wymiarze krajowym i międzynarodowym. Zastosowano również metodę dedukcji. Przeprowadzone rozważania pozwoliły na pozytywną weryfikację tezy. Ponadto pokazały, że pozytywny wizerunek miasta jest istotnym czynnikiem jego rozwoju.
Branding i wizerunek miasta na przykładzie m.st. Warszawy
Keywords: place brand; perceived image; city identity; territorial/place marketing; marka miejsca; postrzegany obraz; tożsamość miasta; marketing terytorialny/miejscowy